2017
DOI: 10.1111/phpp.12296
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic therapy for dermatologic conditions in the pediatric population: a literature review

Abstract: Summary Photodynamic therapy (PDT), using topical aminolevulinic acid (ALA), has been used for years to treat a variety of dermatologic conditions, including actinic keratosis, superficial basal cell carcinoma, and in situ squamous cell carcinoma. While there is a wide range of neoplastic and non‐neoplastic skin diseases for which ALA‐PDT is used in adults, there is a knowledge gap when it comes to its use in children. This review highlights what is currently known regarding the use and efficacy of this therap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 49 publications
0
11
0
Order By: Relevance
“…Photodynamic therapy has been reported as a treatment for pediatric cases with basal cell nevus syndrome, squamous cell carcinoma in‐situ, xeroderma pigmentosum, condyloma acuminatum, plantar warts, acne vulgaris, and linear porokeratosis 16 . However, there is limited reporting and no information regarding long‐term safety of PDT in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Photodynamic therapy has been reported as a treatment for pediatric cases with basal cell nevus syndrome, squamous cell carcinoma in‐situ, xeroderma pigmentosum, condyloma acuminatum, plantar warts, acne vulgaris, and linear porokeratosis 16 . However, there is limited reporting and no information regarding long‐term safety of PDT in pediatrics.…”
Section: Discussionmentioning
confidence: 99%
“…However, there is limited reporting and no information regarding long‐term safety of PDT in pediatrics. The most common reported side effect is pain 16 . Pain can be controlled with cold air, reduced incubation time, and topical or intralesional lidocaine.…”
Section: Discussionmentioning
confidence: 99%
“…For dermatological PDT usually a prodrug is topically applied to the skin, which is then converted by the cells, especially by neoplastic cells, into the actual photosensitizer [44,45]. One prodrug which has been extensively studied is 5-aminolevulinic acid (5-ALA), an endogenous precursor for the heme biosynthesis [46].…”
Section: Photodynamic Therapy For Actinic Keratosismentioning
confidence: 99%
“…ALA makes the skin sensitive for light, consequently it is frequently used for photodynamic therapy in different sorts of dermatologic pathology. In children of 5 years and older, the administration of ALA up to 354 mg, which is over 40 times higher than de 8 mg ALA that was applied on the skin in this study, did not have any side effects ( 23 ). Oral administration of 20 mg/kg ALA in infants of 1 year and older showed a transient increase of alanine aminotransferase ( 24 – 26 ).…”
Section: Discussionmentioning
confidence: 62%
“…ALA is registered for use in adults, for example for photodynamic therapy in dermatologic pathology ( 19 , 20 ) and to visualize brain tumors during fluorescence-guided surgery ( 21 , 22 ) and was not used in pediatric patients until recently. Research with cutaneous ALA administration up to 354 mg in infants of 5 years and older reported no side effects ( 23 ). Oral administration of 20 mg/kg ALA in infants of 1 year and older showed a transient increase of alanine aminotransferase ( 24 – 26 ).…”
Section: Introductionmentioning
confidence: 99%